Automated Quantification of Hydroxyl Reactivities: Prediction of Glycosylation Reactions - Chang, Chun‐Wei; Lin, Mei‐Huei; Chan, Chieh‐Kai; Su, Kuan‐Yu; Wu, Chia‐Hui; Lo, Wei‐Chih; Lam, Sarah; Cheng, Yu‐Ting; Liao, Pin‐Hsuan; Wong, Chi‐Huey; Wang, Cheng‐Chung (Angewandte Chemie International Edition, 2021)
The stereoselectivity and yield in glycosylation reactions are paramount but unpredictable. We have developed a database of acceptor nucleophilic constants (Aka) to quantify the nucleophilicity of hydroxyl groups in glycosylation influenced by the steric, electronic and structural effects, providing a connection between experiments and computer algorithms. The subtle reactivity differences among the hydroxyl groups on various carbohydrate molecules can be defined by Aka, which is easily accessible by a simple and convenient automation system to assure high reproducibility and accuracy. A diverse range of glycosylation donors and acceptors with well‐defined reactivity and promoters were organized and processed by the designed software program “GlycoComputer” for prediction of glycosylation reactions without involving sophisticated computational processing. The importance of Aka was further verified by random forest algorithm, and the applicability was tested by the synthesis of a Lewis A skeleton to show that the stereoselectivity and yield can be accurately estimated. A so‐called “GlycoComputer” program has been developed to foresee and predict the yield and stereoselectivity of glycosylation reactions based on the properties of various donors, acceptors, activation systems and solvents. The program statistically analyzes and compares the relative reactivity value (RRV) of donors and the acceptor nucleophilic constant (Aka) of acceptors.